LEGAL ANALYSIS OF THE CIRCULATION OF COUNTERFEIT OIL IN WEST KALIMANTAN - Agustinus Rian Bhaskoro; Rahman Amin (STAI Nusantara Kota Banda Aceh, 2026)
The circulation of counterfeit motor oil in West Kalimantan has become a growing legal and social issue along with the increasing public demand for motor vehicles. This practice not only causes economic losses to consumers but also threatens vehicle safety and violates the trademark rights of legitimate businesses. This study aims to analyze the forms of counterfeit oil distribution, causal factors, the effectiveness of law enforcement, and its impact on society in West Kalimantan. The research employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving police officers, consumers, and business actors. Data analysis used the Miles, Huberman, and Saldaña model through data reduction, data presentation, and conclusion drawing. The findings indicate that counterfeit oil circulation is influenced by economic factors, low public legal awareness, weak supervision of product distribution, and the rapid growth of digital trade. Law enforcement remains ineffective; therefore, stronger supervision, public legal education, and inter-agency cooperation are necessary to protect consumers and combat counterfeit oil distribution.